ANALISIS YURIDIS PENGATURAN SYARAT PELAKSANAAN DIVERSI PADA TINGKAT PEMERIKSAAN DI PENGADILAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Wayan Agus Singid Adnyana; Ni Luh Gede Astariyani; I Nyoman Bagiastra (Jurnal Komunikasi Hukum, 2024)
In juvenile criminal justice system, there is the diversion policy as the transfer of juvenile cases from judicial process to outside of judicial process. The requirement regulation for diversion implementation are regulated in SPPA Law. However, about the implementation of diversion at Court, there is PERMA Number 4 of 2014 which regulates the requirement for implementing diversion as contrary with SPPA Law. This research aims to do analysis about disharmonization of norms related to regulation of requirement for implementing diversion between SPPA Law and PERMA Number 4 of 2014, and analysis about implementation of PERMA Number 4 of 2014 against SPPA Law. This research used normative legal research methods with legislative regulations approach and conceptual approach. The legal materials used is primary, secondary and tertiary legal materials obtained through document study techniques, and analyzed using deductive methods. The results of this research show that disharmonization of norms between SPPA Law and PERMA Number 4 of 2014, is because PERMA position is below the Legislative Regulations based on hierarchy of Legislative Regulations, but in case examination process at the District Court, PERMA Number 4 of 2014 still enforced and ignoring the SPPA Law with referring to the Supreme Court Law.